2007
DOI: 10.1007/s10029-007-0222-7
|View full text |Cite
|
Sign up to set email alerts
|

Repair of giant incisional abdominal wall hernias using open intraperitoneal mesh

Abstract: Open intraperitoneal mesh repair appears to be a good option for the treatment of complex incisional hernia (at least 10 cm in diameter or multiorificial) in obese patients contraindicated for laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 27 publications
3
18
0
4
Order By: Relevance
“…Staging of the ventral hernia has been helpful in surgical decision and in post-operative comparison of results [13]. The open intraperitoneal technique is appropriate for complex incisional hernias occurring in obese patients, but is contraindicated when laparoscopic access has been obtained; minimal access was shown to be feasible in patients with a larger mesh of 15 cm [14][15][16]. A cellular dermal matrix has been also suggested in this cases to resist to infection as well as porcine [3,17].…”
Section: Discussionmentioning
confidence: 99%
“…Staging of the ventral hernia has been helpful in surgical decision and in post-operative comparison of results [13]. The open intraperitoneal technique is appropriate for complex incisional hernias occurring in obese patients, but is contraindicated when laparoscopic access has been obtained; minimal access was shown to be feasible in patients with a larger mesh of 15 cm [14][15][16]. A cellular dermal matrix has been also suggested in this cases to resist to infection as well as porcine [3,17].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the cited protection of composite prosthetic against intestinal adhesions, it is recommended, whenever possible, bringing the greater omentum between the viscera and prosthesis 1 . Bernard, et al 1 showed in their series of 61 patients using polypropylene mesh coated on the intra-cavity face by PTFEe, satisfactory results with only 5% of recurrence and morbidity rates of around 5% 1.…”
Section: Operative Strategymentioning
confidence: 98%
“…Intent to increase the volume of the abdominal cavity, to enable the re-introduction of the hollow herniated viscera with mesenteric edema by decreasing the the volume of the hollow viscera, with respiratory therapy until cardiorespiratory function improves, the patient does not feel chest discomfort or dyspnea, normalizes blood gas, and intra-abdominal pressure remains lower than 15 cm H2O 11 . Other measures must be taken preoperatively, as the passage of a nasogastric tube with suction to reduce the distension of the bowel and mechanical preparation of the colon 1,11,24 .…”
Section: Preoperativementioning
confidence: 99%
See 1 more Smart Citation
“…The increased physiological stress of the greater operative duration on a patient who often has multiple co morbidities seems to place a significant role in predicting the recurrences outcome [9,10]. This physiological stress seems to be directly correlated with the physic and tensile strength and it is an important concept because in this case, the authors pointed out that the physiological stress during the surgery but forgot to mention the physiological stress of the patient before the surgery that creates the situation that brought the patient to surgery [11][12][13].…”
Section: The Clinical Issuesmentioning
confidence: 99%